2010
DOI: 10.1089/ten.tea.2009.0837
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Microenvironment Modulates Neural Stem Cell Survival, Migration, and Differentiation

Abstract: Biomaterial matrices presenting extracellular matrix (ECM) components in a controlled three-dimensional configuration provide a unique system to study neural stem cell (NSC)-ECM interactions. We cultured primary murine neurospheres in a methylcellulose (MC) scaffold functionalized with laminin-1 (MC-x-LN1) and monitored NSC survival, apoptosis, migration, differentiation, and matrix production. Overall, MC-x-LN1 enhanced both NSC survival and maturation compared with MC controls. Significantly lower levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 45 publications
4
64
0
Order By: Relevance
“…13,20 Furthermore, it is well-known that extracellular matrix (ECM) components play a role in the differentiation of NSCs into neurons. 29,30 Our data showed that the rate of Map2-positive cells was higher in the PLGA-SF group than in the PLGA-only group. These results not only demonstrated the known function of NT-3 in neuronal survival and differentiation, but also suggested that SF may contribute to the differentiation of neurons.…”
mentioning
confidence: 64%
“…13,20 Furthermore, it is well-known that extracellular matrix (ECM) components play a role in the differentiation of NSCs into neurons. 29,30 Our data showed that the rate of Map2-positive cells was higher in the PLGA-SF group than in the PLGA-only group. These results not only demonstrated the known function of NT-3 in neuronal survival and differentiation, but also suggested that SF may contribute to the differentiation of neurons.…”
mentioning
confidence: 64%
“…Biointerfacial display of neurotrophic factors has the potential to significantly influence neural cell behaviors relevant to CNS repair, including adhesion, differentiation, and neurite extension [51,52]. In this study, we investigated multiple presentation schemes for the neural cell adhesion molecule L1 to elucidate the effects of presentation on primary neurons and human embryonic stem cellderived NPCs on 2-D and 3-D polymer substrates.…”
Section: Discussionmentioning
confidence: 99%
“…NPCs express the major integrin for laminin, α6β1, which promotes differentiation of hESCs to neurons in vitro (Ma et al, 2008;Stabenfeldt et al, 2010). When collagen I hydrogels containing fibronectin or laminin were compared for delivery of fetal-derived NSCs, laminin-containing gels resulted in increased cell survival 8 weeks posttransplantation compared to those with fibronectin (Tate et al, 2009).…”
Section: Cell Survivalmentioning
confidence: 99%